Stockhausen as CEO: The Executive Model of Interpretive Labour. - Carithers, Kirsten Speyer (Contemporary Music Review)
Building upon research on the performance practices engendered in avant-gardism of the mid-to-late twentieth century, this essay introduces a theoretical framework for the creative work of realising experimental music, here labeled interpretive labour (IL). The Executive model of IL is discussed in detail, bringing together ideas about authorship, representation, and exploitation. Performances of Karlheinz Stockhausen's Plus Minus (1963) provide an ideal case study for this issue, as historical performances highlight the challenges inherent in its realisation. Drawing on these performances' sketches, archival recordings, and reception history, it becomes apparent that Stockhausen is effectively outsourcing his compositional responsibilities in this work, suggesting the usefulness of radically reframing indeterminate music performance-practice as a mode of production.